A global phylogenetic analysis of trap‐jaw ants, Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae: Ponerinae). (7th April 2021) - Fernandes, Itanna O.; Larabee, Fredrick J.; Oliveira, Marcio L.; Delabie, Jacques H. C.; Schultz, Ted R.
Abstract: We present a phylogeny of the trap‐jaw ant genera Anochetus and Odontomachus with dense taxon sampling representing all biogeographical regions and all species groups for both genera. Four nuclear protein‐coding genes ( Long‐wavelength rhodopsin, Topoisomerase I, Wingless and Rudimentary ) and one mitochondrial gene ( cytochrome oxidase I) were sequenced for 221 individuals of Anochetus (44 species) and Odontomachus (38 species). Analyses using Bayesian and maximum‐likelihood criteria recovered essentially the same phylogenetic relationships, including strongly supported reciprocal monophyly of both genera. The analyses recovered nine of the 12 species groups previously proposed for Odontomachus and nine of the 22 species groups previously proposed for Anochetus. Based on these results, species groups are redefined . Anochetus contained an additional new, previously unrecognized group defined here as the hohenbergiae group. Divergence‐time analyses estimated the clade composed of Odontomachus  +  Anochetus arose during the early Paleocene, with Odontomachus and Anochetus diverging during the Eocene. Biogeographic analyses suggest that the most recent common ancestor (MRCA) of Odontomachus and Anochetus occupied either the Neotropical or Afrotropical region during the late Cretaceous and that the two genera radiated during the early Paleocene. The ancestor of Odontomachus originated in the Neotropical or Afrotropical regions, giving rise to lineages that radiated during the late Eocene, and the ancestor of Anochetus originated in the Neotropical region, giving rise to lineages that radiated during the early Eocene. Abstract : We tested the informal species groups of Odontomachus and Anochetus . We employed divergence‐time estimates and biogeographic analyses for the genera. Anochetus hohenbergiae retains the most plesiomorphies of any Anochetus species.